Design And Building Furniture Sales Web Based Application at CV. Azaria Abadi Permai. - Wicaksono, Arif; Sulistiowati, Sulistiowati; Kusumawati, Weny Indah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV .Azaria Abadi Permai is a manufacturing company of furniture made fromwood base. A furniture produced from the company that are located in Jetis,Mojokerto areas is a closet , the table , a chair , a rack versatile and custom furniture that as requested by customers. Furniture products are distributed to different cities in Indonesia and foreign country.Currently the process of furniture sales to the customers can only be achieved by telephone, e-mail and coming directly into the company .The impact from that is customers it mostly comes from the other city must first waiting for the information about ordered furniture products. In addition, interactions among the associated with the furniture selling process now has not computerized well, so the data and information that relating to the selling process is still not organized. Solutions to solve the problem is designing and building web based application of furniture sales. With the web based furniture sales application, customers should have known the information about the ordered furniture easily.This application is also made to help interaction companies to the customers and the interaction among parts of CV.Azaria Abadi Permai so therefore data and information that relating to the furniture selling process can be well managed. Keywords : Furniture Sales, Web Based Sales Application.